The Influence Of Motivation, Compensation, And Work Environment On The Performance Of Human Resources In Zakat Management Institutions: Organizational Commitment As An Intervening Variable In Zakat Institutions Of Pasuruan City - Akhmad Khalim; Dwi Cahyono; Toni Herlambang (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the effects of work motivation, compensation, and work environment on the performance of human resources (HR) working in zakat management institutions in Pasuruan City, with organizational commitment serving as an intervening variable. A quantitative approach with a survey method was employed in this research. The study population consisted of employees from five zakat institutions in Pasuruan City, namely BAZNAS Pasuruan City, Yatim Mandiri, LAZISMU, LAZISNU, and Baitul Maal Hidayatullah. Data were collected through questionnaires distributed to 154 respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 5.0 software. The findings reveal that work motivation and compensation do not significantly influence either organizational commitment or employee performance. In contrast, the work environment has a positive and significant effect on both organizational commitment and employee performance. Furthermore, organizational commitment is found to have a positive and significant impact on employee performance. The mediation analysis indicates that organizational commitment does not mediate the relationship between work motivation and employee performance, nor the relationship between compensation and employee performance. However, organizational commitment significantly mediates the effect of the work environment on employee performance. The results suggest that the work environment is the most influential factor in enhancing both organizational commitment and employee performance within zakat management institutions. Therefore, zakat institutions should prioritize the development of a supportive, safe, and comfortable work environment to strengthen organizational commitment and improve employee performance effectively.